The novel PI3 kinase inhibitor, BAY 80‐6946, impairs melanoma growth in vivo and in vitro. Issue 8 (August 2014) - Schneider, Philine; Schön, Margarete; Pletz, Nadin; Seitz, Cornelia S.; Liu, Ningshu; Ziegelbauer, Karl; Zachmann, Karolin; Emmert, Steffen; Schön, Michael P.
Abstract Due to its almost universal resistance to chemotherapy, metastasized melanoma remains a major challenge in clinical oncology. Given that phosphatidyl inositol‐3 kinase (PI3K) activation in melanoma cells is associated with poor prognosis, disease progression and resistance to chemotherapy, the PI3K‐Akt signalling pathway is a promising therapeutic target for melanoma treatment. We analysed six human melanoma cell lines for their constitutive activation of Akt and then tested two representative lines, A375 and LOX, for their susceptibility to PI3K‐inhibition by the highly specific small molecule inhibitor, BAY 80‐6946. In addition, the effect of BAY 80‐6946 on A375 and LOX melanoma cells was assessed in vivo in a xenotransplantation mouse model. We provide experimental evidence that specifically inhibiting the PI3K pathway and phosphorylation of Akt by this novel compound results in antitumoral activities including inhibition of proliferation, induction of apoptosis and cell cycle arrest in vitro and in vivo. However, the susceptibility did not show a clear‐cut pattern and differed between the melanoma cell lines tested, resulting in in vivo growth inhibition of A375 but not LOX melanoma cells. Thus, in some cases BAY 80‐6946 or related compounds may be a valuable addition to the therapeutic armamentarium.